Behavioral Dynamics in Implementation and Challenges in PT. Sky Energy Indonesia Tbk Responsibility Accounting - Aulia Gandini; Sri Trisnaningsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze behavioral dynamics in the implementation of responsibility accounting and identify the challenges faced by PT Sky Energy Indonesia Tbk in the financial and operational context. This study is a case study analysis by collecting data through company annual report and the latest news to understand the financial condition, governance and operational challenges faced by the company. The research results show that PT. Sky Energy Indonesia Tbk experienced a decline in sales, faced a Postponement of Debt Payment Obligation (PKPU) process, and was at risk of being delisted from the Indonesian Stock Exchange (BEI), which was exacerbated by the impact of the COVID-19 pandemic. Although annual reports demonstrate a commitment to transparency and sustainability, the findings indicate a gap between commitments and actual practices. This research recommends that to overcome this challenge, PT. Sky Energy Indonesia Tbk needs to increase transparency, operational efficiency, focus on renewable energy, strengthen governance, and develop a solid financial strategy. These steps require a strong commitment from companies to adaptation, innovation and long-term sustainability. This research provides insight into the importance of responsibility accounting in facing financial and operational challenges, as well as contributing to the literature on corporate governance and sustainability in Indonesia.